Yield Performance, Laying Behaviour Traits and Egg Quality of Purebred and Hybrid Hens Reared under Outdoor Conditions - Chiara Rizzi (Animals, 2020)
This study compared the yield performance, laying behavioural traits and egg quality of purebred and hybrid hens (from 28 until 44 weeks of age, considering four periods) reared under outdoor conditions. The four genotypes were reared on the same trial station, on four areas (one genotype/area), and under the same environmental conditions from hatching until the end of the trial. Italian dual-purpose purebred (Ermellinata di Rovigo—ER and Robusta maculata—RM) and hybrid (Hy-Line Brown—HB and Hy-Line White 36—HW) hens (flock size: 70 birds/genotype) were allowed outdoors (4 m2/bird, good pasture during the growing period and poor pasture throughout the laying period, according to the season) and indoors (0.20 m2/bird, five birds/individual nest) and fed commercial feed. Significant (p < 0.01) differences among genotypes were found. The hybrids showed a higher laying rate and hen-day edible egg mass, and a lower body weight than the purebreds. Broken and out-of-nest egg% were higher in RM and HW than ER and HB, respectively. Double-yolk egg% was higher in hybrids than in purebreds. The eggshell colour varied among brown eggshell ER, RM, and HB. The ER showed the lowest shape index. With aging, the yolk to albumen ratio linearly increased in all groups, eggshell% changed in ER, HW, RM (cubic) and in HB (linear). The purebreds showed meat spots% higher than blood spots; HW showed the lowest total inclusion%. In conclusion, according to an egg scoring evaluation (egg weight = medium-large size, yolk to albumen ratio = 0.5, total inclusions = none), HW showed a higher quality than HB and RM, and ER was intermediate. The RM hens showed the highest% of defective eggs, especially for overcrowding at nest, HB showed the lowest. Under outdoor conditions the laying behaviour of the purebred hens and the nest management are important factors for the saleable egg rate.